2022
DOI: 10.1080/08897077.2020.1732512
|View full text |Cite
|
Sign up to set email alerts
|

Improving Medical Students’ Attitude toward Patients with Substance use Problems through Addiction Medicine Education

Abstract: Background: Patients with addiction often encounter negative attitudes from health care professionals, including medical doctors. Addiction medicine training might improve medical students' attitudes toward patients with addiction problems and change the way they think about addiction. We evaluated the effect of comprehensive addiction medicine training on students' attitudes and illness perceptions and explored which perceptions are most relevant for attitude development. Methods: In a quasi-experimental non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
(149 reference statements)
0
10
0
Order By: Relevance
“…Structured education that focuses on opioid use disorder treatment and emphasises recovery, as well as programs that include contact with patients in one-on-one or small group settings, has been found to decrease stigma and increase confidence and interest in providing OAT in later practice. [101][102][103] Much has been written about the need to address the restrictive and coercive elements of OAT delivery. 39,40,68 The recent introduction of long-acting injectable depot buprenorphine may offer an alternate approach to how OAT treatment could be delivered.…”
Section: Dovepressmentioning
confidence: 99%
“…Structured education that focuses on opioid use disorder treatment and emphasises recovery, as well as programs that include contact with patients in one-on-one or small group settings, has been found to decrease stigma and increase confidence and interest in providing OAT in later practice. [101][102][103] Much has been written about the need to address the restrictive and coercive elements of OAT delivery. 39,40,68 The recent introduction of long-acting injectable depot buprenorphine may offer an alternate approach to how OAT treatment could be delivered.…”
Section: Dovepressmentioning
confidence: 99%
“…Another quasi‐experimental non‐randomized study among 296 fourth‐year students using the Medical Condition Regards Scale showed that addiction medicine training improved students' attitudes toward patients with addiction, reduced demoralized perception, and increased the perception of a coherent understanding of addiction. This study concluded that addiction medicine training was effective in improving attitudes of medical students toward patients with addiction and their perception of addiction (Ayu et al, 2020). Pal Singh Balhara and Singh (2019) documented the feasibility, acceptability and effectiveness of an online course to strengthen the knowledge, skills, and attitude of the participants on behavioral addictions involving Internet use.…”
Section: Resultsmentioning
confidence: 99%
“…of the 17 studies included in this review, eight explored the effect and perceptions of training in addiction psychiatry/medicine (Ayu et al, 2020;Pal Singh Balhara & Singh, 2019;Chikezie et al, 2021;Khan et al, 2020;Mahadevan et al, 2020;Mehrotra et al, 2018;Nolan et al, 2018;Pahuja et al, 2020). A descriptive evaluation of a novel grant funding mechanism for tobacco training programs showed that 19 grants were awarded by Global Bridges to organizations in low-and middle-income countries across all six WHO regions.…”
Section: Impact and Perception Of Training In Addiction Psychiatrymentioning
confidence: 99%
“…Addiction medicine training in the form of didactic and experiential learning is associated with increased knowledge and improved attitudes toward patients with SUD among medical students and trainees [ 54 56 ]. There is a growing array of resources available for medical providers who are interested in gaining knowledge and skills in addiction treatment, short of completing a fellowship.…”
Section: Additional Resources For Gaining Addiction Medicine Knowledg...mentioning
confidence: 99%